Mitochondrial DNA copy number as a mediator of the relationship between insulin resistance and cognitive function in patients with euthymic bipolar disorder - Tsung Han Tsai; Cheng Ying Wu; Cheng Chen Chang; Ta Tsung Lin; Chin San Liu; Po See Chen (Kaohsiung Journal of Medical Sciences)
Abstract Persistent cognitive challenges in bipolar disorder (BD) may be tied to insulin resistance, which crucially affects both metabolism and brain health. Additionally, mitochondrial DNA (mtDNA) copy number has emerged as an indicator of cognitive performance and response to treatment in BD. However, it remains unclear whether and how this indicator might serve as a bridge between metabolic dysfunction and cognitive capacity. In 68 study participants with euthymic BD, insulin resistance was assessed according to fasting glucose and insulin levels. mtDNA copy number was quantified from leukocytes, and executive function was measured with the Wisconsin card‐sorting test (WCST). Mediation models were applied to explore the statistical relationship between insulin resistance, mtDNA copy number, and executive function. Both linear regression and Poisson distribution approaches with robust bootstrap simulations were used for significance testing. The results indicated that insulin resistance indirectly affects executive function via mtDNA copy number. This mediation relationship was statistically significant for both preservation errors and completion of categories in the WCST, although there were no significant direct effects of insulin resistance on the executive functions. We therefore concluded that insulin resistance is associated with reduced mtDNA copy number in blood, which may negatively impact executive functions in patients with euthymic BD. Further work is warranted to determine if improving metabolic and mitochondrial health may lead to better cognitive outcomes in BD.